Severe hypotension induced by Almonertinib: a case report with literature review and clinical insights - Niu, Haiyu; Song, Feixue; Zhou, Xiaochun; Jin, Qiaoying; Liu, Yating; Luo, Benxin; Wei, Hanwen (Frontiers in Oncology, 2025)
Lung adenocarcinoma is a common malignancy in clinical practice, but the coexistence of lung and gastric adenocarcinomas in a single patient is rare. This report presents the case of a 70-year-old male with a history of smoking for over 30 years, diagnosed with both lung adenocarcinoma and gastric adenocarcinoma through lung biopsy and gastroscopy. Following comprehensive evaluations and exclusion of treatment contraindications, the patient underwent a therapeutic regimen comprising Sintilimab combined with nab-paclitaxel and cisplatin. Genetic testing of the lung cancer tissue identified mutations in the epidermal growth factor receptor (EGFR) gene, specifically p.L858R in exon 21 and p.T790M in exon 20. Consequently, the patient was prescribed Almonertinib at a dose of 110 mg/day to target these mutations. Approximately 72 h after initiating Almonertinib, the patient developed dizziness and nausea, accompanied by hypotension (blood pressure: 80/58 mmHg). Echocardiographic findings and NT-proBNP levels indicated no structural cardiac abnormalities or significant dysfunction. Almonertinib was discontinued, but subsequent attempts to reintroduce the drug consistently resulted in hypotension. After cardiology specialists evaluation, the hypotension was attributed to Almonertinib, prompting its permanent discontinuation. The treatment was adjusted to replace Almonertinib with Furmonertinib at a dose of 80 mg/day for lung adenocarcinoma, while maintaining the initial immunotherapy and chemotherapy regimen for gastric adenocarcinoma. Following these adjustments, the patient experienced no recurrence of hypotension. This case report reviews the literature to explore potential mechanisms of Almonertinib-induced hypotension and offers insights into the prevention, diagnosis, and management of similar adverse events in clinical practice.